Current status of prison privatization research on American prisons and jails - Gaes, Gerald G. (Criminology & public policy, 2019)
Private companies manage 8.4% of the U.S. prison population and 5.4% of the jail population. On average, the costs and quality of privatized facilities seem to be about the same as publicly operated prisons, but the lack of high‐quality studies limits a strong inference. Although states with increases in prison privatization have lower public‐sector costs, this may be a result of strong cost controls, not of their level of privatization. An increase in recidivism seems to occur for people placed in private facilities. This assertion is based on the findings of several studies in which regression controls are used and on only one study in which a strong counterfactual design is applied. Finally, there is no evidence that prison privatization was responsible for the dramatic growth in incarceration that peaked in 2009.